Blockchain efficient Byzantine fault tolerance consensus algorithm for IIoT - LI Fengqi; SONG Qingqing; XU Hui; DU Xuefeng; GAO Jialong; TONG Ning; WANG Deguang (Tongxin xuebao)
Considering the malicious risks associated with diverse terminals in the industrial Internet of things (IIoT), a practical Byzantine fault tolerant (PBFT) efficient consensus algorithm based on credit score and dynamic double layer (CD-PBFT) was proposed to meet the requirements of high efficiency and security fault tolerance in the consensus process. The participation of good nodes in the consensus and the removal of faulty nodes were ensured by the credit score model. The parallelism of transaction verification and read write operations was achieved through the implementation of a double layer architecture. Nodes with high credit were randomly selected as the master node by the adaptive master node algorithm, ensuring its security. Experimental results show that CD-PBFT not only can maintain the safety and liveness of the consensus algorithm but also can reduce network delay by 34.8% and increase throughput by 25.2% compared with PBFT, which meets the double requirements of efficiency and security fault tolerance.